The bear in the attic - McManus, Patrick F. (Henry Holt, 2002)
Starting with his trademark outdoorsman's wit, Patrick F. McManus ponders the strange allure of the RV, the existential implications of being lost, the baffling tendency of animals to outsmart those who wish to hunt them, and the singular pleasure of doubling the size of every fish one doesn't actually catch. McManus brilliantly captures the everyday absurdities that comprise our existence. Alongside his humor, McManus's inimitable vision consistently evokes a childlike wonder at the natural world. Even if we are running low on food, the compass is broken, and we are fairly certain we have just spotted a family of Sasquatches frolicking in the treetops, The Bear in the Attic makes the outdoors seem wildly irresistible.